Aging of polyethylene thermoplastic liner exposed to sulfuric acid corrosive environments. Issue 3 (April 2021) - Liu, Chongyang; Tang, Chenhuai; Wang, Shenghui
Abstract: Thermoplastics have been widely used as liners of pressure vessels and pressure pipes to improve corrosive resistance in recent years. During long-term use under complex circumstances of corrosive medium, high temperature and existence of oxygen, gradual aging of thermoplastic was often observed. However, the aging mechanism of thermoplastic under such complex condition is rarely reported. In this study, various methods such as dynamic mechanical analysis (DMA), differential scanning calorimetry (DSC), fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and tensile tests were performed to examine the aging mechanism of polyethylene (PE) liner used for different times under various temperatures and concentrations of acid. The results reveal that aging of liner material resulted from swelling due to exposure to acid in low concentrations during long-term use, which will result in surface damage, even leakage of acid and decrease in PE strength. Recrystallization under concentrations higher than 50% is observed, it is accompanied by increase in melting point (Tm ), decomposition temperature, tensile strength and change of transparency. With further increase in acid concentration, change of molecular structure was observed in FTIR spectrums, which might be the result of oxidation, dehydrogenation and chain breaking induced by high concentration of acid.